AKTIVITAS BIODESULFURISASI DIBENZOTIOFENA DALAM MODEL MINYAK TETRADEKANA PADA RASIO MINYAK AIR DAN KONSENTRASI RESTING SEL ISOLAT BAKTERI SBJ8 - Putra Pratama, I Gede Krisna; Wayan Gunam, Ida Bagus; Ganda Putra, G.P. (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 5 No 1 (2017): Maret)
This study aims to determine the best ratio of oil / water and concentration of resting cells and determine the time course of resting cells bacteria  isolates SBJ8  to be known the biodesulfurization capability in two-phase media using media mineral salt sulfur free-tetradecane (MSSF-TD). Oil/water  ratio used in this study is 1 : 1 , 1 : 2 and 1 : 4 in combination with cell concentration by OD 660 10, 20,  and 30. The  study was conducted using 200  mg ·  l –1 dibenzothiophene as a source of sulfur dissolved in tetradecane as a  model of petroleum (oil phase). Isolates were incubated for 24 hours  at 37°C and the residue analyzed by  gass cromathography mass selective (GC-MS).  Testing the degradation of resting cells is accomplished by two replications.  The results showed that the ratio of  oil water 1 : 4 by and cell concentration OD 660 30 shows the results of the highest degradation of 84.84% and the time course of 24 hours resting cells show degradation rate dibenzothiophene up to 81.84%. Keywords :  Biodesulfurization, dibenzothiophene, tetradecane, resting cells
Keywords: 126,